2004
DOI: 10.1016/j.nuclphysa.2004.05.015
|View full text |Cite
|
Sign up to set email alerts
|

A model finding a new Richardson potential with different scales for confinement and asymptotic freedom, by fitting the properties of Δ++ and

Abstract: Phenomenological Richardson potential has built in asymptotic freedom (AF in short) and confinement, with only one parameter Λ in the potential. But it is known that the scales of AF and confinement are not the same. In the present work a relativistic mean field calculation for baryons is tried out with two parameters Λ and Λ ′ for AF and confinement respectively .To test the two parameter potential we calculate the energies and the magnetic moments, of the triple u -quark system (∆ ++ ) and the triple s -quar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 24 publications
(27 reference statements)
2
20
0
Order By: Relevance
“…One EOS (SS1) obtained by Dey et al (1998) using an unmodified Richardson Potential with both Λ and Λ equal to 100 MeV. matter (our present work) and the properties of confined 3u and 3s baryons (Bagchi et al 2004). Although the confinement part Λ is stronger, leading to a sharp surface, it is softened by medium effects, developing a screening length.…”
Section: Conclusion and Summarymentioning
confidence: 63%
See 1 more Smart Citation
“…One EOS (SS1) obtained by Dey et al (1998) using an unmodified Richardson Potential with both Λ and Λ equal to 100 MeV. matter (our present work) and the properties of confined 3u and 3s baryons (Bagchi et al 2004). Although the confinement part Λ is stronger, leading to a sharp surface, it is softened by medium effects, developing a screening length.…”
Section: Conclusion and Summarymentioning
confidence: 63%
“…Indeed, for self bound high density strange quark matter, Dey et al (1998) found that Λ needed to be ∼100 MeV. In the present paper, proper scales are chosen for both the parameters, as determined from a calculation by Bagchi et al (2004) by fitting the masses and recently determined magnetic moments of Ω − and ∆ ++ . In Sect.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, strange star properties have been calculated with a modified Richardson potential, which has different scales for AF and confinement. The scale values were obtained from baryon magnetic moment calculations (Bagchi et al 2004). In this model, chiral symmetry restoration at high density is incorporated by introducing density‐dependent quark masses.…”
Section: Mean Field Model For Strange Starsmentioning
confidence: 99%
“…A baryonic system like stars can be explored in relativistic tree level calculation with a potential which may be obtained from the meson sector phenomenology in (Witten 1979) using 1/ N C theory. We have done this with Richardson potential – modified to have different scales for AF and confinement–deconfinement mechanism (CDM) with parameters are fitted from baryon magnetic moments (Bagchi et al 2004). So there are no free potential parameters left in SS calculations.…”
Section: The Modelmentioning
confidence: 99%
“…Λ′ is the scale parameter corresponding to confinement as the third term reduces to a linear confinement for small q . From Bagchi et al (2004), we get Λ= 100 MeV and Λ′= 350 MeV. The modified potential is used in SS calculation (Bagchi et al 2005).…”
Section: The Modelmentioning
confidence: 99%